2008
DOI: 10.1074/jbc.m804084200
|View full text |Cite
|
Sign up to set email alerts
|

p21 Ras/Impedes Mitogenic Signal Propagation Regulates Cytokine Production and Migration in CD4 T Cells

Abstract: The propensity of T cells to generate coordinated cytokine responses is critical for the host to develop resistance to pathogens while maintaining the state of immunotolerance to selfantigens. The exact mechanisms responsible for preventing the overproduction of proinflammatory cytokines including interferon (IFN)-␥ are not fully understood, however. In this study, we examined the role of a recently described Ras GTPase effector and repressor of the Raf/MEK/ERK cascade called impedes mitogenic signal propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
(33 reference statements)
1
13
0
1
Order By: Relevance
“…Hypomorphic studies (described below) have shown that this is not simply an artifact of overexpression. Transcriptional activation through ERK is likewise inhibited, as shown in reporter assays with Elk-1 (26), c-Fos (6), and NF-AT (26). The inhibitory function of IMP appears to be specific for the ERK pathway as other kinases such as JNK (c-Jun N-terminal kinase) and Akt are not affected (6).…”
Section: Threshold Controlmentioning
confidence: 77%
See 3 more Smart Citations
“…Hypomorphic studies (described below) have shown that this is not simply an artifact of overexpression. Transcriptional activation through ERK is likewise inhibited, as shown in reporter assays with Elk-1 (26), c-Fos (6), and NF-AT (26). The inhibitory function of IMP appears to be specific for the ERK pathway as other kinases such as JNK (c-Jun N-terminal kinase) and Akt are not affected (6).…”
Section: Threshold Controlmentioning
confidence: 77%
“…Furthermore, immunofluorescence analysis revealed that IMP recruits KSR to distinct subcellular compartments, which is reversed upon Ras activation (6). Interestingly, IMP that has been modified with a CAAX motif (and is thus localized to the cell membrane) is an even more effective ERK pathway inhibitor than unmodified IMP; the CAAX effect is further enhanced in the IMP(C264A) mutant (26). This may suggest that the site of action of IMP is near the membrane, which is consistent with its roles in suppressing membrane localization of KSR1 complexes and as a Ras effector.…”
Section: Regulation Of Ksrmentioning
confidence: 95%
See 2 more Smart Citations
“…BRAP is also known to impede mitogenic signal propagation (IMP), the threshold modulator of the Raf-mitogen-activated protein kinase-extracellular signal regulated kinase (Raf-MEK-ERK) signal pathway (12). By repressing the Raf-MEK-ERK signal cascades, BRAP influences the secretion of interferon-γ in CD4 T cells (13). However, its role in the cardiovascular system remains to be explored.…”
mentioning
confidence: 99%